2018
DOI: 10.1111/ppl.12860
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid promotes root system development in birch tissue culture: a comparison to aspen culture and conventional rooting‐related growth regulators

Abstract: The research aim was to assess the effects of the plant hormone abscisic acid (ABA) and the growth regulator paclobutrazol (PBZ) on root system development during the in vitro culture of different birch and aspen genotypes. The studied genotypes involved two aspen (Populus tremula and Populus tremuloides × P. tremula) and two silver birch (Betula pendula) trees, with one of the birches characterized by its inability to root in vitro. For experiments, apical shoot segments were cultured on nutrient medium enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…In another study, ABA was applied in conditions of water deficiency and enhanced UVB radiation to improve the acclimation of grapevine ( Vitis vinifera ) to cultivation at high heights, and the treatment resulted in more than six-fold increased accumulation of squalene—the precursor of triterpenoids [ 36 ]. In plant in vitro cultures, ABA is used to enhance the production of phenolic acids in Salvia miltiorrhiza Bunge [ 29 ]; however, more often, it has been reported as a factor applied in various tissue culture systems to promote somatic embryogenesis, enhance somatic embryo quality or promote root system development [ 37 , 38 ]. The results obtained in the present study indicated that ABA can act as an efficient enhancer of the triterpenoid productivity in plant in vitro cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, ABA was applied in conditions of water deficiency and enhanced UVB radiation to improve the acclimation of grapevine ( Vitis vinifera ) to cultivation at high heights, and the treatment resulted in more than six-fold increased accumulation of squalene—the precursor of triterpenoids [ 36 ]. In plant in vitro cultures, ABA is used to enhance the production of phenolic acids in Salvia miltiorrhiza Bunge [ 29 ]; however, more often, it has been reported as a factor applied in various tissue culture systems to promote somatic embryogenesis, enhance somatic embryo quality or promote root system development [ 37 , 38 ]. The results obtained in the present study indicated that ABA can act as an efficient enhancer of the triterpenoid productivity in plant in vitro cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Other hormone signaling pathways are also known to affect rooting. For example, ABA is known to promote root development in birch ( Betula pendula ) and aspen ( Populus tremula ) (Vaiciukyne et al., 2019). We found many ABA‐related DEGs with low expression in Mx‐A cuttings compared with Mx‐J cuttings, which was inconsistent with the previous report (Saito et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The role of gibberellins (GAs) in AR formation is still unclear but a few studies have demonstrated that exogenous applications of gibberellic acid are inhibitors of AR formation in Populus . In the aspen P. tremula , the application of paclobutrazol (PBZ), an inhibitor of GA biosynthesis, was found to promote AR formation, whereas GA treatment had a negative effect on AR development in in vitro culture cuttings ( Žiauka and Kuusiene, 2010 ; Vaičiukynė et al, 2019 ). Moreover, transgenic hybrid aspen P. tremula × P. tremuloides overexpressing GA20ox1 , one of the genes that catalyzes the final step in the synthesis of bioactive GAs, had poor rooting efficiency, whereas overexpression of the GIBERELLINS INSENSITIVE ( GAI ) gene, which is a repressor of GA signaling, increased the number of ARs ( Eriksson et al, 2000 ; Busov et al, 2006 ; Mauriat et al, 2014 ).…”
Section: Endogenous Factors Influencing Rooting Of Cuttingsmentioning
confidence: 99%
“…Moreover, gene expression of ARF6 and ARF8 , positive regulators of adventitious rooting, was increased, whereas the expression of ARF17 , a negative regulator of adventitious rooting, was significantly lower at the base of the stem cuttings ( Tomiyama et al, 2020 ). In Populus , Vaičiukynė et al (2019) measured the content of ABA in in vitro cultured shoots of two aspens ( P. tremula , and P. tremuloides × P. tremula ) with different rooting abilities. No differences in ABA content were found between the two genotypes, suggesting that the endogenous content of ABA in the shoots is not correlated with the rooting ability of these two genotypes.…”
Section: Endogenous Factors Influencing Rooting Of Cuttingsmentioning
confidence: 99%